Barriers and determinants of consistent offering of HPV vaccination by healthcare facilities - Ikponmwosa Osaghae; Onyema Greg Chido-Amajuoyi; Banda A. A. Khalifa; Sanjay Shete (Taylor & Francis Group, 2023)
Expanding access to HPV vaccination is critical to increasing HPV vaccine uptake. We assessed the determinants and barriers to consistent offering of HPV vaccine among healthcare facilities. This was a cross-sectional survey of healthcare providers (HCPs) in Texas. Prevalence of the reasons healthcare practices do not consistently offer HPV vaccination was estimated. Multivariable regression analyses were conducted. Of 1169 HCPs included in the study, 47.5% (95% CI: 44.6-50.3%) reported their practices do not provide HPV vaccination or do not offer it consistently. Compared to physicians, nurses had 77% lower odds (Adjusted Odds Ratio (AOR): 0.23, 95% CI: 0.16-0.32, p-value: < .001), and physician assistants had 89% lower odds (AOR: 0.11, 95% CI: 0.07-0.16, p-value: < .001) of their healthcare practices consistently offering HPV vaccination. Compared to university/teaching hospitals, the odds of healthcare practices consistently offering HPV vaccination were 44% lower (AOR: 0.56, 95% CI: 0.35-0.91, p-value: 0.019) in solo practices but 266% higher (AOR: 3.66, 95% CI: 2.04-6.58, p-value: < .001) in FQHC/public facilities. The common reasons healthcare practices do not consistently offer HPV vaccination were; HPV vaccination is not within the scope of the practice (48.1%), referrals to other clinics (27.7%), and limited personnel (11.4%). Non-physicians were more likely to report that HPV vaccination was not in their scope and to refer patients than physicians. Moreover, solo practices were more likely to report challenges with acquisition and storage of the vaccine and referral of patients as reasons for not consistently offering HPV vaccination than university/teaching hospitals, FQHC/public facilities, or group practices. System-level interventions including training of non-physicians and expansion of practice enrollment in programs that support HPV vaccine acquisition and storage are needed.